The controverted therapeutic efficacy of Allium sativum and Artemisia herba-alba extracts on Cryptosporidium-infected mice - Elbahaie, Enas Said; El Gamal, Reda Lamei; Fathy, Ghada Mahmoud; Al-Ghandour, Asmaa Mohammed Farouk; El-Akabawy, Nadia; Abd El Hameed, Basma Hosny; Yahia, Samah Hassan (The Journal of Infection in Developing Countries, 2023)
Introduction: Cryptosporidiosis has become an issue of great interest being life-threatening among immunocompromised hosts worldwide. This study explored the curative effect of Allium sativum (garlic) and Artemisia herba-alba ethanolic extract versus Nitazoxanide drug on both immunocompetent and immunosuppressed-Cryptosporidium experimentally-infected mice. Methodology: One hundred male Swiss albino mice were divided into the following groups: (GI) non-infected non-treated group, (GII) infected non-treated group, (GIII) garlic treated group, (GIV) A. herba-alba treated group, (GV) Nitazoxanide treated group, each group subdivided into two subgroups (a) Immunocompetent, (b) immunosuppressed. The assessment was performed by parasitological counting of fecal oocysts, histological examination of intestinal tissue, immunological detection of interferon-gamma levels in mice sera, and ultrastructural study by transmission electron microscopy. Results: Garlic and A. herbal-alba extracts showed a decrease in the mean oocyst counts through all days of follow-up. This was associated with significant up-regulation of interferon-gamma cytokine levels in serum and histological improvement in intestinal tissues of mice compared to control groups and the results were confirmed by transmission electron microscopy. The highest efficacy was obtained by garlic, then by A. herbal-alba extracts followed by Nitazoxanide treated group; where the immunocompetent groups showed better improvement than immunosuppressed ones. Conclusions: Garlic has a perfect effect as a promising therapeutic agent against Cryptosporidiosis and therefore validates their traditional use in parasitic infections. Accordingly, it may offer a good option for cryptosporidium treatment in immunocompromised patients. They could be used as a natural safe product for the preparation of a new therapeutic agent.